Tritium Records to Trace Stratospheric Moisture Inputs in Antarctica. Issue 6 (25th March 2018) - Fourré, E.; Landais, A.; Cauquoin, A.; Jean‐Baptiste, P.; Lipenkov, V.; Petit, J.‐R.
Abstract: Better assessing the dynamic of stratosphere‐troposphere exchange is a key point to improve our understanding of the climate dynamic in the East Antarctica Plateau, a region where stratospheric inputs are expected to be important. Although tritium ( 3 H or T), a nuclide naturally produced mainly in the stratosphere and rapidly entering the water cycle as HTO, seems a first‐rate tracer to study these processes, tritium data are very sparse in this region. We present the first high‐resolution measurements of tritium concentration over the last 50 years in three snow pits drilled at the Vostok station. Natural variability of the tritium records reveals two prominent frequencies, one at about 10 years (to be related to the solar Schwabe cycles) and the other one at a shorter periodicity: despite dating uncertainty at this short scale, a good correlation is observed between 3 H and Na + and an anticorrelation between 3 H and δ 18 O measured on an individual pit. The outputs from the LMDZ Atmospheric General Circulation Model including stable water isotopes and tritium show the same 3 H‐δ 18 O anticorrelation and allow further investigation on the associated mechanism. At the interannual scale, the modeled 3 H variability matches well with the Southern Annular Mode index. At the seasonal scale, we show that modeled stratospheric tritium inputs in the troposphere are favored in winter cold and dry conditions. Key Points: Tritium records in three snow pits at Vostok show natural variability at about 10 years (solar cycles) and at a shorter periodicity From measurements on a same pit at same depths, tritium is found to be correlated to Na + and anticorrelated to δ 18 O Modeled tritium outputs suggest that this correlation is at least partly linked to atmospheric conditions modulating input of stratospheric air